Importance of Feedback, Training and Media Format for Students' Reflective Practice - Barbara Therese Miller; Larssyn Staley (International School for Social and Business Studies, 2021)
Purpose: The purpose of this student-centred study is two-fold: to better understand how students perceive the role of reflection in their learning, both for their degrees and for their development as future leaders and how lecturers can best use feedback, training and various media to support and encourage student development. Study design/methodology/approach: A class of undergraduate students were surveyed at the beginning and end of a semester on their preferred learning styles. Follow-up interviews were also held with selected participants. During the semester, students were exposed to various formats of reflection: individual written reflections, video reflections and peer reflections. Students received both training in reflection and feedback on their reflections. In the survey and interviews, students were asked about the perceived benefits of such learning formats for their current studies and future careers. Findings: Students indicated an increased ability to reflect honestly and confront their weaknesses. Students also indicated a stronger preference for either the individual written reflection or the video reflection over the peer reflection. Students saw benefit in the greater time that an individual written reflection provided as well as the multimodal aspects of the video reflection, which helped them to reflect in a new way. Additionally, the feedback students received played a big role in allowing the students to feel more comfortable and reflect more honestly. Originality/value: Previous studies have focused on a variety of factors that affect students' perception of reflection. This study takes a closer look at the effect of feedback and media format on students' perceived benefits. https://www.doi.org/10.53615/2232-5697.10.31-40